The technology-culture interface and its impact on aviation safety: a North African perspective. - Belaid, Zakria Abdulhamid Gamudi (Cranfield University, 2018)
The aviation industry in the North Africa Region (NAR) is still suffering from a high rate of fatal accidents in comparison to other regions. In 2016, about 128 passengers were killed in the Middle East and NAR, whereas in Europe just two passengers killed despite both regions using a similar aircrafts. Aviation companies within the NAR thus require safety performance improvement. The current research indicates that pilot decision-making performance in the cockpit is responsible for about 60% of aviation fatal accident in the global aviation industry. In addition, the current literature shows that pilots’ risk perception is directly influenced by the culture interface, which plays crucial role in shaping their decision-making performance. Accordingly, this study investigated the national culture impact on pilot decision-making performance in the cockpit within the NAR. A number of professional pilots from the NAR were surveyed and interviewed to explore this phenomenon. A mixed method research approach was implemented in this study, where 143 professional pilots from different levels were surveyed and 12 semi-structured interviews were conducted, to discover the extent to which these pilots are effect by the technology–culture interface within the NAR. The research investigated this phenomenon mainly based on four themes: cultural attributes, attitude to human and organisational factors, automation and risk perception; these are shown by the literature to be the most significant factors affecting the pilot risk perception in the cockpit. Ten factors were investigated, in addition to assessing the collective pilot’s risk perception within the NAR. The result indicated that NAR pilots are negatively affected by power distance, teamwork and automation as direct implications of the technology–culture interface. In addition, these pilots are suffering from high tolerance and acceptance of risk as an indirect impact of the regional national culture. Therefore, as the aim of this research is to enhance the pilot’s decision-making performance in the cockpit, a guideline for cultural calibration of the Crew Resource Management (CRM) training programme was proposed. This cultural calibration relies on development of the CRM curriculum by enhancing the pilot non-technical skills to overcome the effects of the technology–culture interface in the region. It also aims to improve their risk perception through introducing training in domain-specific risky events in the cockpit, which should enhance their ability to identify the cues that exist in risky situations. Furthermore, the limited research of aviation authorities and aviation safety departments’ roles regarding monitoring and enforcing the safety regulations and implementing proactive safety programmes in the aviation companies within the NAR negatively affect the progress of improving the safety performance.
Keywords: Pilot decision making; risk perception; culture; technology-culture; automation; teamwork; power distance